„Nowe znamiona” Kościoła według papieża Franciszka - Artemiuk, Przemysław (Warszawskie Studia Teologiczne, 2023)
The article is devoted to selected elements of the ecclesiology of Pope Francis. The author notices numerous ecclesiological threads that allow to collect and systematize the papal thoughts about the Church. They form an ecclesiology that has its sources, has characteristic features and areas of interest. Looking at the teaching of Francis from the perspective of fundamental ecclesiology, the author of the article finds four original features in him, as it were, "new features" of the Church. They are poverty, solidarity, peripherality and charity. Each of them is theologically justified by Francis and embedded in the papal ministry.